Implementasi Metode Forward Chaining Pada Pengembangan Game Edukasi Warisan Budaya - Muhammad Bambang Firdaus; Ummul Hairah; Arief Hidayat; Andi Tejawati; M Khairul Anam; Nariza Wanti Wulan Sari (METIK JURNAL, 2021)
Indonesia is an archipelagic country with various types of cultural heritage, including traditional houses, traditional folk dances and musical instruments. However, today with the rapid advancement of technology, the existing cultural heritage is starting to be abandoned because of the large number of foreign cultures entering this country. The author carried out this research aimed at reintroducing cultural heritage to the community through media in the form of games that are adaptive to the players, one of which is by using the forward chaining method in its development. In practice, the forward chaining method is used to determine whether the player has the right to continue to the next level or not. Based on the results of the questionnaire obtained, it shows that 92.5% of respondents strongly agree that this game can help users get to know more about cultural heritage in Indonesia and 82.9% of respondents strongly agree that this game is interesting to play.